The Hidden Costs of Statelessness: Educational Challenges for Indonesian Children in Philippines Migrant Settlements - Weol, Wolter; Rumbay, Christar; Sendiang, Imee (Pelopor Publikasi Akademika, 2025)
This research qualitatively investigates the difficulties that Indonesian migrant children in the Philippines encounter while attempting to obtain higher education due to incomplete citizenship records, financial difficulties and institutional restrictions. Children, parents, educators, and government officials who were interviewed pointed out that statelessness of children remains an issue today besides financial difficulties and bureaucratic constraints. Programs of Sekolah Indonesia Davao (SID) and Indonesian Consulate of Davao (KJRI) exist to help students, but most students still cannot go to college because of both legal and financial problems. This report recommends targeted legislative reforms, strengthened bilateral cooperation as well as community-driven initiatives toward improving access to education for this marginalized population.